Crick, Crack, Crow! - Lord, Janet; Paschkis, Julie, 1957- (Atlanta : Margaret Quinlin Books, Peachtree, 2024)
An American crow leaves his large extended family and flies to the nearby farm, where he finds lots of fun and trouble. Includes facts about crows.
Ages 4-8.
Grades K-1.
Keywords: American crows -- Fiction; Crows -- Fiction; Animal fiction; Picture books